Elliptical shaft excavation and furnishing in response to depth induced ground pressure - Sturgis, G.A.; Berberick, D.R.; Board, M.P.; Strickland, W.H.; Swanson, M.T. (Deep Mining 2017: Proceedings of the Eighth International Conference on Deep and High Stress Mining, 2017)
Hecla Limited is nearing completion of the Lucky Friday mine No.4 shaft located in Mullan, Idaho. The shaft is collared at the 4940 Level of the mine and will have a final mine level depth of 8620, or 2,923 m (9,590 ft) below the surface. After reaching the 7400 Mine Level the shaft encountered ground deformation higher then allowed for in the design for a circular shaft excavation and concrete lining. This additional ground deformation required portions of the shaft concrete liner to be reinforced with frameless, steel liner plate. To eliminate the installation of the liner plate from the remaining shaft development, the design of the shaft excavation starting at the 7650 Mine Level was changed to an elliptical cross-section based on the overall stress field orientation as well as the orientation of the structure of the host rock surrounding the shaft. The elliptical cross-section was instrumented to confirm the shaft excavation and lining was performing as designed. This design change has allowed the shaft to continue to the planned 8620 Mine Level without the need to install liner plate in the shaft or change the overall functionality of the shaft or the Lucky Friday lifeofmine plan.